Comparative study of rice morphological and physiological characteristics of rice grown under organic and inorganic farming - Safrudin, Amad; Dewi, Ratna; Dulbari, Dulbari (Kultivasi, 2024)
Organic farming practices have shown a potential to improve rice yields, aside from the popular conventional ones. This study aimed to comparatively analyze the morpho-physiological characteristics of rice plants grown under organic and inorganic farming. This research was conducted at the Polinela Organic Farm experimental station (5°21'10"S 105°13'43"E, 114 m sea above level), from February to April 2023 using a completely randomized design. The results showed that rice grown organically exhibited a notably higher chlorophyll index and actual water use efficiency compared to those grown inorganically. Conversely, inorganic farming resulted in a greater number of tillers than organic farming. However, there were no significant differences between the two systems regarding CO2 efficiency and plant height. An interesting fact is the improved water use efficiency by organic farming helps rice plants to achieve similar growth performance while requiring less water.